SINTASAN LARVA UDANG GALAH DARI SUMBER GENETIK YANG BERBEDA - Ani Rimalia; Yulius Kisworo; Mukhlisah Mukhlisah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
This research aim to studi was to survival rate of the giant fresh water prawn from genetic resources pagatan river, Kintap river and Barito river. The methot used this reserch was experimental design with completly random design (3X3). The results showed to the best survival rate from genetic resources pagatan with SR=93,07%, surviva rate genetic resources Barito with SR=90,40% and surviva rate genetic resources Kintap with SR=86,93%